IMPLEMENTATION OF SMART ECO RETAIL WITH THE CARBON FOOTPRINT APPROACH IN BUILDING SUSTAINABLE GREENHOUSE MANAGEMENT AT NGAJUM MALANG PRISON - Soseco, Thomas; Wulandari, Dwi; Fajariant, Otto; Kusuma, Fuad Indra; Gunawan, Ari; Syafruddin, Afis Baghiz; Indriati, Nur (FEBI UIN Sunan Gunung Djati Bandung, 2025)
Sustainable agricultural management is very important in facing climate change and natural resource degradation. Carbon footprint as a carbon emission measurement tool can help reduce the environmental impact of farming activities, especially in greenhouse management. This study aims to develop a carbon footprint-based smart eco-retail model to build sustainable greenhouse management while developing agricultural skills for inmates at Ngajum Malang Prison. Smart eco retail is a retail concept that integrates digital technology with environmentally friendly principles to support efficient and sustainable distribution of agricultural products. This model prioritizes carbon footprint measurement and management as an effort to reduce carbon emissions throughout the production and distribution chain. In addition to environmental aspects, this model also focuses on empowering inmates through modern agricultural skills training that supports the principle of sustainability. The research method uses a Research and Development (R&D) approach with stages of needs analysis, design, implementation, and evaluation. Data were collected through observation, interviews, and documentation at Ngajum Prison. Training and implementation of the model involved the active participation of inmates as the main subjects. The results of the study indicate that carbon footprint-based smart eco retail can create more environmentally friendly and efficient greenhouse management. Inmates have succeeded in improving agricultural skills integrated with green technology. This model provides dual benefits, namely improving the quality of farm products and social empowerment of residents. The study recommends the development of a broader model with the integration of more advanced digital technology to optimize greenhouse management in various institutions.